Development of Monopoly-Based Media Using Game-Based Learning to Improve Elementary School Students’ Learning Outcomes - Naura Nisrina Afifah; Dewi Nilam Tyas (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
This research is based on the low achievement of science learning outcomes for fourth-grade students at Wonosari 03 Elementary School in Semarang City, which is caused by the lack of engaging concrete media, resulting in relatively low student activity levels, despite teachers' efforts to implement active learning models. The purpose of this study is to develop and test the feasibility and effectiveness of Monopoly media based on Game-Based Learning to improve students' cognitive science learning outcomes on flora and fauna topics in Indonesia. This research method uses a Research and Development approach with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Data collection was conducted through observation, interviews, questionnaires (including media and material expert questionnaires, as well as teacher and student questionnaires), documentation, and tests (pretest and posttest). The data analysis techniques used in this research include descriptive statistics, normality tests, paired-samples t-tests, and N-Gain tests. The results indicate that the developed media is considered highly feasible by media experts (95%) and material experts (93%). This is supported by teacher response questionnaires at 95% and student response questionnaires at 93.75%. The normality test indicates that the pre-test and post-test data are normally distributed, so a paired-samples t-test was conducted, yielding a p-value of 0.000 (< 0.05), indicating a significant difference in learning outcomes before and after the media implementation. The N-Gain test shows a value of 69.70% (moderate effectiveness). It can be concluded that the monopoly media on Game-Based Learning about the diversity of flora and fauna in Indonesia, developed, is considered very feasible and sufficiently effective in improving students' cognitive learning outcomes in grade IV IPAS at Wonosari 03 Public Elementary School in Semarang City.